Anti-HER2 antibody prolongs overall survival disproportionally more than progression-free survival in HER2-Positive metastatic breast cancer patients. (October 2021) - Chen, I-Chun; Hu, Fu-Chang; Lin, Ching-Hung; Huang, Shu-Min; Chang, Dwan-Ying; Cheng, Ann-Lii; Lu, Yen-Shen
Abstract: Background: This meta-analysis aimed to test the hypothesis that the HER2-positive metastatic breast cancer (mBC) patients treated with anti-HER2 antibodies in trial intervention arms have a greater prolongation of overall survival (OS) than of progression-free survival (PFS) and this extra-prolongation of median survival time in OS relates specifically to the anti-HER2 antibody. Methods: The NCBI/Pubmed and Cochrane databases were searched systematically for HER2-positive or mBC trials published in English during January 1999–November 2017. Treatment arms with shorter PFS were considered as the "control" arm, whereas those with longer PFS as the "test" arm. The between-treatment drug differences were grouped into nine categories. Groups with or without anti-HER2 antibodies were pooled respectively for comparisons. The interrelationships between PFS and OS hazard ratios (HRs) and median survival time differences were investigated by conducting fixed-effects and mixed-effects linear meta-regression analyses. Results: Twenty-eight trials (10, 928 patients) from 438 articles were collected, and four with missing data were excluded in meta-regression analysis. Overall median PFS (HR = 0.73, 95% CI: 0.68–0.78) and median OS (HR = 0.82, 95% CI: 0.77–0.87) weakly favored the longer PFS arm with a weak correlation between the PFS and OS HRs. However, the between-treatment drug difference was anti-HER2 antibody, the absolute increment in median OS time was double that of median PFS time ( p  < 0.001) and linearly correlated, which was not found with any non-anti-HER2 antibody drug differences. Conclusions: Anti-HER2 antibody in patients with HER2-positive mBC prolonged OS more than PFS and mandates further investigation. Highlights: Our study dissected the overall survival benefit over progression-free survival in HER-2 positive metastatic breast cancer treated with anti-HER2 antibody by meta-analysis. Use of anti-HER2 antibodies, but not other anticancer drugs, to treat HER2-positive metastatic breast cancer independently predicted the OS compared with PFS. The design of future clinical trials should consider anti-HER2 antibodies carefully in the treatment armamentarium for HER2-positive metastatic breast cancer.